Baseball-Related Craniofacial Injury Among the Youth: A National Electronic Injury Surveillance System Database Study. Issue 4 (June 2022) - Kaplan, Nate; Kim, Minji; Slavin, Benjamin; Kaplan, Lee; Thaller, Seth R.
Abstract : Background: Baseball is 1 of the most played sports among adolescents in the United States. Yet, youth baseball players experience the greatest numberoforal and facial injuries, compared to other athletes involved in other sports. Methods: The National Electronic Injury Surveillance System was analyzed for all hospital admissions for youth baseball athletes (5–19-year-old) experiencing a baseball-related craniofacial injury. These included concussions, head contusions, head lacerations, facial contusions, facial fractures, facial hematomas, face lacerations, eye contusions, mouth lacerations, dental injuries, and neck contusions. Descriptive statistics were performed, and injury incidence was described by sport, injury type, and age group. Results: Nearly half of the injuries (45.0%) occurred among 10- to 14-year-old patients, followed by 5- to 9-year-olds and 15- to 19-year-olds. Of all age groups, the most common type of injury was facial contusions, compromising one fourth of the injuries. Other frequent injuries included facial lacerations (19.9%), facial fractures (19.7%), and concussions (13.4%). Conclusions: Overall, this analysis underscores the need for increased implementation of protective equipment, such as faceguards and safety balls. Although facial fractures are less common amongst the pediatric population, physicians and coaches need to be better educated about the most frequent injury patterns and management. Further prospective studies are warranted to better characterize these findings and to prevent injuries.